Plautyńskie maski w komedii „La Cassaria” Ludovica Ariosta - Stachowicz , Klaudia (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2020)
The aim of the paper is to indicate the common features of the characters of Ludovico Ariosto’s Renaissance comedy La Cassaria with their Plautine prototypes. The article explores, therefore, how Roman concepts went onto influence Ariosto with regards to character creation and the use of names that belong to the category of nomen omen.